Kontribusi Identitas Etnis dan Identitas Akademik terhadap Subjective Well-Being Mahasiswa - Zakki Nurul Amin; JT. Lobby Loekmono; Afriyadi Sofyan; Vira Mulyawati (Program Studi Bimbingan dan Konseling FKIP UMSU, 2020)
College is an accumulation of social-academic components that interact with each other and are pluralistic. Positive interaction between social and academic components can support individual well-being. This study focuses on the psychological construct (subjective well-being) of Javanese college students on two main sources of students, the social component (ethnic identity) and the academic component (academic identity). Partially, the results of this study indicate that only academic identity has a significant relationship with subjective well-being (r = 0.33, p <0.01). While using multiple linear regression analysis shows the results that ethnic identity and academic identity have a significant contribution to subjective well-being (F = 8.83, p <0.01). This finding has implications for primary student services to improve student subjective well-being.